2018
DOI: 10.1080/02713683.2018.1472285
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Endothelial Changes in Behçet’s Patients with Inactive Ocular Involvement

Abstract: Ocular attacks in our BD patients may have caused permanent changes in the corneal endothelial layer. However, these changes did not lead to corneal decompensation, but further studies are necessary to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…When comparing BD patients with and without ocular involvement, their result showed that sub-basal nerve plexus density was significantly lower, and nerve tortuosity was significantly higher in the BD with ocular involvement group. Similar results regarding the decrease of endothelial cell density in BD patients have been reported using specular microscopy [13] and ICVM [14], as well as increased corneal thickness in the BD patients using ultrasound pachymetry [15]. The current study confirmed these results using IVCM and further expanded the knowledge by increasing the study population, by adding second control group as BD without ocular involvement and also by shining a light on the sub-basal nerve plexus tortuosity.…”
supporting
confidence: 87%
“…When comparing BD patients with and without ocular involvement, their result showed that sub-basal nerve plexus density was significantly lower, and nerve tortuosity was significantly higher in the BD with ocular involvement group. Similar results regarding the decrease of endothelial cell density in BD patients have been reported using specular microscopy [13] and ICVM [14], as well as increased corneal thickness in the BD patients using ultrasound pachymetry [15]. The current study confirmed these results using IVCM and further expanded the knowledge by increasing the study population, by adding second control group as BD without ocular involvement and also by shining a light on the sub-basal nerve plexus tortuosity.…”
supporting
confidence: 87%
“…28 It was reported that ocular inflammation negatively affects corneal endothelial functions and increases corneal thickness, and in another study, corneal endothelial changes were even observed in Behçet’s patients without ocular involvement. 29,30 Uric acid deposition in the anterior chamber has been previously demonstrated in individuals with gout. 31 Uremic toxins can disrupt the balance between both proinflammatory and inflammatory factors and proapoptotic and apoptotic factors.…”
Section: Discussionmentioning
confidence: 93%
“…17 Ozdamar et al reported increased thickness in active uveitis in Behcet's disease than inactive and control Group. 18 Cankaya et al reported decreased CD and HEX in inactive period inpatient of Behcet's disease, but no difference in CCT was seen. 19 Similarly, uveitis, but there was no difference in CCT1, whereas, in our study, we observed that there was a statistically significant difference between the Groups and patient with uveitis had increased corneal thickness (CCT) than healthy subjects.…”
Section: Discussionmentioning
confidence: 95%